2020
DOI: 10.33418/ataunikkefd.782142
|View full text |Cite
|
Sign up to set email alerts
|

Pandemi̇ (Covi̇d-19) Süreci̇ndeki̇ Uzaktan Eği̇ti̇m Uygulamalarina İli̇şki̇n Li̇sansüstü Öğrenci̇ Görüşleri̇

Abstract: Öz Bu çalışmanın amacı, Covid-19 sürecinde yürütülen uzaktan eğitim uygulamalarını lisansüstü öğrenimine devam eden öğrencilerin görüşlerine göre değerlendirilmektir. Araştırma bir durum çalışmasıdır. Çalışmada Çanakkale Onsekiz Mart Üniversitesi bünyesinde yer alan Eğitim Bilimleri Enstitüsü'nde öğrenim gören gönüllü 14 öğrenciden öğrenci günlükleri yoluyla veriler toplanmıştır. Günlük yazan 14 öğrenci içinden yine gönüllülük esasına göre belirlenen 7 kişiden yarı yapılandırılmış görüşme formları kullanılarak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 16 publications
3
7
0
4
Order By: Relevance
“…At this stage, a new word group was not formed and words like asocial life, staying away from people, being a test subject, last chance, side effects, medicine, biological weapon, desperation, low motivation, boring lessons, insufficient internet quota, time problem, and inappropriate homework were annexed to the existing word pool. These word groups (Çakın & Külekçi-Akyavuz, 2020;Genç et al, 2020) and subwords have been declared in several studies in the literature (e.g., ETF, 2020; Kaçan & Gelen, 2020;Karakuş & Yanpar-Yelken, 2020;Şen & Kızılcalıoğlu, 2020) and hence similar results appear to have been attained.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…At this stage, a new word group was not formed and words like asocial life, staying away from people, being a test subject, last chance, side effects, medicine, biological weapon, desperation, low motivation, boring lessons, insufficient internet quota, time problem, and inappropriate homework were annexed to the existing word pool. These word groups (Çakın & Külekçi-Akyavuz, 2020;Genç et al, 2020) and subwords have been declared in several studies in the literature (e.g., ETF, 2020; Kaçan & Gelen, 2020;Karakuş & Yanpar-Yelken, 2020;Şen & Kızılcalıoğlu, 2020) and hence similar results appear to have been attained.…”
Section: Discussionsupporting
confidence: 78%
“…Another cluster of qualitatively oriented studies in the literature is the word association tests. To cite some of these, the work of Çakın & Külekçi-Akyavuz (2020), Genç et al, (2020), Kaçan & Gelen (2020), Karakuş & Yanpar-Yelken, (2020) and Şen & Kızılcalıoğlu (2020) through which these researchers propounded words and word groups associated with the pandemic period, and also with the predominant components of the pandemic can herein be enlisted. Aside from the mentioned studies another array of qualitative research seems to center on interviews with the participants.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Ancak pandeminin yarattığı psikolojik baskı, sosyalleşememe ve alışılagelen eğitim kültürünün yüz yüze sınıf eğitimi biçiminde olması sebebiyle öğrencilerin önemli bir kısmı, yapılan değerlendirmelerde çevrimiçi eğitimin verimli olmadığı yönünde görüş bildirmişlerdir (Bozkurt A. , 2020;Ezginci, 2020;Keskin & Özer Kaya, 2020). Diğer yandan eğitimcilerin de önemli bir kısmı da, teknoloji kullanımı konusundaki yetkinliklerinin online sisteme hızlı geçiş için yeterli olmasına rağmen bu geçiş sürecinde sınıf eğitimlerini çevrimiçi sınıflarda web kameraları aracılığıyla doğrudan simule etmeleri sebebiyle eğitimlerin veriminin düştüğü yönünde değerlendirmelerde bulunmuşlardır (Ezginci, 2020;Yılmaz, Güner, Mutlu, & Arın Yılmaz, 2020;Genç, Engin, & Yardım, 2020). Bu sonuçlarla karşılaşılmasının başlıca sebebleri; öğretmenler, eğitim yöneticileri ve devlet yetkilileri gibi eğitim dünyasındaki karar alıcı diğer paydaşların, çevrimiçi eğitim ve e-öğrenme kavramlarını bu döneme kadar ikincil yardımcı öğrenme araçları olarak değerlendirmesi, bu alanlarda yapılacak çalışmaları yeterince önemsememesi ve alınması gereken aksiyonları ötelemiş olması olarak değerlendirilebilir (Bilgiç Doğan, 2014).…”
Section: Literatür Taramasiunclassified
“…It has been observed that the increase in the use of different technological applications for communication during the pandemic process accelerates the communication between student-student, student-teacher (Chang & Satako, 2020). Additionally, teachers who have been open to communication, have supported students, and have had the idea of giving feedback quickly caused an increase in communication between students and teachers (Genç et al, 2020). However, students who stated that their communication with their teachers decreased, indicated that they could not receive feedback and meet with their teachers during the distance education process.…”
Section: Discussionmentioning
confidence: 99%